2018
DOI: 10.1002/smll.201803000
|View full text |Cite
|
Sign up to set email alerts
|

Microsphere‐Based Nanoindentation for the Monitoring of Cellular Cortical Stiffness Regulated by MT1‐MMP

Abstract: Biophysical properties are intimately connected to metastatic functions and aggressiveness in cancers. Especially, cellular stiffness is regarded as a biomarker for the understanding of metastatic potential and drug sensitivity. Here, protease‐mediated changes of cortical stiffness are identified due to the deformation of cytoskeleton alignment at a cortex. For the past few decades, membrane type 1‐matrix metalloproteinase (MT1‐MMP) has been well known as a kernel protease enriched in podosomes during metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Accordingly, HT-1080 cells were incubated on PNHC for 6 h, and we analyzed the images of PNHC before and after treatment ( Figure 7 a,b). We confirmed that several cells were attached well and were largely elongated on the PNHC surface, indicating that the cells were under active metabolism (for example, glycolysis) [ 38 ]. The B/G values were extracted from around the attached cells in the image and compared with those of the bare PNHC.…”
Section: Resultsmentioning
confidence: 53%
“…Accordingly, HT-1080 cells were incubated on PNHC for 6 h, and we analyzed the images of PNHC before and after treatment ( Figure 7 a,b). We confirmed that several cells were attached well and were largely elongated on the PNHC surface, indicating that the cells were under active metabolism (for example, glycolysis) [ 38 ]. The B/G values were extracted from around the attached cells in the image and compared with those of the bare PNHC.…”
Section: Resultsmentioning
confidence: 53%
“…We measured the nanomechanical strength of the HAP/Col hydrogels using the 10.8 μm polystyrene-bead tip. Because the size of the AFM probe tip is much larger than the pore of each hydrogel, it is assumed that the diverse pore size of the hydrogel hardly influenced the estimation of the nanomechanical properties of the HAP/Col hydrogels …”
Section: Resultsmentioning
confidence: 99%
“…21 Eventually, the investigation of the change of cytoskeletal network is critical to anticipate the survival of cancer patients. Extending our previous study on the cytoskeletal network for cancer cells, 22 thus, we have focused on the change of cytoskeletal network from cancer cells treated with phenolics-loaded nanocarriers.…”
Section: T H Imentioning
confidence: 99%